Therapeutic Effectiveness of Curcuma longa (Turmeric) Beverage on Reducing Dysmenorrhea Pain - Rahmawati, Annisa Mufida; Ningrum, Novi Budi; Kuswandari, Eti; Aisyah, Fitria; Ummah, Wiqodatul (Medico Insight Innovation Initiative, 2024)
Dysmenorrhea or painful menstruation is a gynecological problem that is most experienced by women of various ages. On average, more than 50% of women experience it. Turmeric is believed to contain natural ingredients active ingredients that can function as analgesics, antipyretics and anti-inflammatories. This study examines the impact of Curcuma longa (turmeric) drink therapy on dysmenorrhea pain reduction among female adolescents at Poltekkes Wira Husada Nusantara. Employing a one-group pretest-posttest design, 50 students were assessed for dysmenorrhea severity before and after a three-day treatment with turmeric drinks. Results indicate a significant decrease in pain level post-treatment, with the average pain score reducing from 6.20 to 13.13 in the experimental group, compared to the minimal change in the control group (from 7.07 to 8.20). Statistical analysis revealed a t-value of 8.254 for the experimental group (p < 0.001), confirming the efficacy of turmeric in alleviating menstrual pain. These results support the use of turmeric drinks as an effective remedy for reducing menstrual pain and suggest further investigation into its broader applications in menstrual health management.